ANALISIS PROGRAM TAX AMNESTY PERIODE PERTAMA SAMPAI KETIGA DALAM UPAYA PENINGKATAN PENERIMAAN PAJAK PADA KANTOR DIREKTORAT JENDERAL PAJAK WILAYAH SUMATERA UTARA I - Annisa Nauli Sinaga; Benny Rojeston Marnaek Nainggolan (Jurnal Akrab Juara, 2018)
Tax revenue is the main thing. With the existence of this tax amnesty program, it is expected that each layer can be used for good tax and tax governance programs for the tax directorate general. The type of research used is descriptive research, in the form of words or verbal from people. To analyze the implementation of tax amnesty in Indonesia a qualitative method with a descriptive exploratory approach is used. To clarify the description of the opportunities, challenges and weaknesses of the implementation of tax amnesty in Indonesia. SWOT Analysis (Strengths, Weaknesses, Opportunities and Threats).